2021
DOI: 10.3389/fped.2021.675238
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events and Unsuccessful Intubation Attempts Are Frequent During Neonatal Nasotracheal Intubations

Abstract: Background: Intubation of neonates is difficult and hazardous. Factors associated with procedure-related adverse events and unsuccessful intubation attempts are insufficiently evaluated, especially during neonatal nasotracheal intubations.Objective: Aim of this study was to determine the frequency of tracheal intubation–associated events (TIAEs) during neonatal nasotracheal intubations and to identify factors associated with TIAEs and unsuccessful intubation attempts in our neonatal unit.Methods: This was a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
2
14
1
1
Order By: Relevance
“…Our fourth finding was that VL use was associated with lower TIAEs. This is consistent with a recently published single-site observational study by Tippmann et al where VL use was predictive of an intubation encounter without TIAEs [ 29 ]. Our study adds strength to this finding with its larger sample size and multicenter design.…”
Section: Discussionsupporting
confidence: 92%
“…Our fourth finding was that VL use was associated with lower TIAEs. This is consistent with a recently published single-site observational study by Tippmann et al where VL use was predictive of an intubation encounter without TIAEs [ 29 ]. Our study adds strength to this finding with its larger sample size and multicenter design.…”
Section: Discussionsupporting
confidence: 92%
“…Neonatal intubation is an essential procedure that all neonatologists need to be competent and proficient in performing. The procedure in this population is complicated not just by the small size of the baby but also by the unique physiology of the newb,orn which leads to decreased reserve and less apnoeic tolerance during laryngoscopy 10–16. As infants are surviving at lower gestational ages and birth weights than before, the procedure is only likely to become more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure in this population is complicated not just by the small size of the baby but also by the unique physiology of the newb,orn which leads to decreased reserve and less apnoeic tolerance during laryngoscopy. [10][11][12][13][14][15][16] As infants are surviving at lower gestational ages and birth weights than before, the procedure is only likely to become more challenging. As the difficulty increases, procedural experience is decreasing due to greater use of non-invasive ventilation, a reduction in working hours and significantly increased numbers of not just trainees but also consultants.…”
Section: Discussionmentioning
confidence: 99%
“…VL improved the view of the glottis in both uncomplicated and difficult intubation situations, increased the success rate in the first attempt at intubation, and reduced the rate of complications, such as damage to oral structures, bradycardias and brief hypoxia (7)(8)(9)(10)(11)(12). Furthermore, several studies in children have confirmed the advantages of VL in difficult intubation conditions and the possibility to reduce TIAEs (tracheal intubation associated events) (13)(14)(15). In particular, VL has shown that it is a suitable and helpful tool for teaching inexperienced medical professionals (13,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%